Effect Analysis Focus Group Discussion to the Level of Knowledge and Attitude of the Bajo Community Working Area Wowonii Health Center - Hasnawati, Hasnawati; Supodo, Timbul; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2023)
Introduction: Direct observation of people who live above the sea, there are people who do not use soap when cleaning themselves because they bathe directly in the sea and they throw their garbage at sea. This is because people's knowledge is still lacking regarding their actions in throwing garbage at sea so that it makes the sea polluted where sea water is used for personal hygiene including washing and there are 70% of people using septic tanks openly that go directly to the sea. Method: The design used by the researcher is pre-experimental using a pretest-posttest model with the aim of finding the effect of focus group discussion. The population as many as 82 people and the number of samples as many as 68 people with sampling using random sampling. Result: Earned p-value = 0.000 < 0.05 Ho is rejected, this shows that Ho is rejected and Ha is accepted which means that there is an influence of knowledge through giving Focus Group Discussion and value 0.000 <0.05 which means that there is a significant influence between attitudes towards giving focus group discussion (FGD) in an effort to prevent dermatitis in the Bajo community in the Wawonii Health Center Work Area. Conclusion: There is a significant influence between knowledge and attitudes through treatment focus group discussion on the prevention of dermatitis in the Bajo community in the working area of the Wawonii Public Health Center